Equality and poverty: views from managers and professionals from public services and household heads in the Belo Horizonte Metropolitan Area, Brazil - Viviane Helena de França; Celina Maria Modena; Ulisses Eugenio Cavalcanti Confalonieri (BMC, 2020)
Abstract Background Tackling poverty requires reconsideration of quantitative factors related to "who" is poor and by "how much" and qualitative factors addressing "what poverty means in these individuals' lives". Greater understanding is required concerning the types of access actually used by families in poverty in attempts to meet their basic needs. Poverty must be addressed based on the question: "Inequality of what?" It is in reflecting on the realities of such groups when their basic needs are not met that public policies can be improved and implemented with legitimate priorities. Objective: Describe coverage and access to public health, education and social assistance services and the related effects on the quality of life of families in extreme poverty. Methods An exploratory mixed methods study was conducted applying Amartya Sen's "Basic Capability Equality" framework, with: 1) 27 interviews with managers and professionals from public services serving territories with extreme poverty; 2) Survey with a systematic proportionate stratified sample of 336 heads of households in extreme poverty from a total 2605 families. The resulting data was analyzed with thematic content analysis and descriptive statistics, respectively. Results The managers and professionals described the lives of families in extreme poverty with phrases such as, "These people suffer. Sadness weighs on their lives!" and "Depression is the most common illness". Their precarious circumstances and inadequate access were cited as causes. Quality of life was considered bad or very bad by 41.4% of heads of households. A total income of less than one-third of the minimum wage was received by 56.9% of the sample. One or more people were unemployed in the family in 55.8% of cases. For 53.3% of heads of households, public services "did not meet any or few of their needs". The main social determinants of health were described as: alcohol and drugs (68.8%); lack of good health care (60.7%); and absence of income/work (37.5%). The following were identified as solutions to improve their quality of life: (1) health (40.5%); (2) education (37.8%); and (3) employment (44.6%). Conclusions The social determinants of poverty and health must be addressed jointly through intersectoral public policies and egalitarian mechanisms that promote investment in social protection.